Adaptive Compensation for Time-Slotted Synchronization in Wireless Sensor Network - Tengfei Chang; Qin Wang (International Journal of Distributed Sensor Networks)
Since time division multiple access (TDMA) is employed to reduce power consumption, time synchronization is critically important for wireless sensor networks. Packet-based clock correction is one of main methods to maintain synchronization among nodes. However, in many real cases, such as industrial equipment monitoring and diagnosis, there is no need to exchange messages during relatively long time, while highly accurate time synchronization has to be maintained, which results in that additional packets have to be exchanged specifically for synchronization purpose. For addressing this problem, an adaptive compensation method is proposed in this paper to achieve a high synchronization precision without exchanging message frequently. We proved that the adaptive compensation method can achieve a high synchronization precision with much fewer packet exchanges. In addition, the performance of the proposed scheme has been evaluated in three different experimental settings. In the indoor experiment, compared with the synchronization method without using compensation, 98% of the synchronizing packets can be eliminated while maintaining synchronization precision at 100  μ s. In the outdoor experiment with higher temperature fluctuation, 80% of the packets can be eliminated with 100  μ s synchronization precision. In the case of sudden temperature changes of more than 10 ° C, the proposed compensation packet frequency regresses to the frequency of the synchronization method without compensation.